2020
DOI: 10.3390/jcm9103218
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Oral Manifestation: An Observational, Human Study

Abstract: The correlation between SARS-CoV-2 and oral manifestations is still controversial. The aim of this observational study was to determine the oral manifestation of the hospitalized patients for COVID-19. A total of 20 patients met the inclusion criteria and gave their signed informed consent. A questionnaire of 32 questions regarding the oral and systemic health condition was administrated to these patients during the convalescence. A descriptive statistic was performed. Data were analysed through the use of χ2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
2
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 41 publications
9
89
2
13
Order By: Relevance
“…In COVID-19, the impaired salivary gland secretions are often associated with xerostomia and taste loss (69). Xerostomia is the subjective complaint of oral dryness, while salivary gland hypofunction is an objective matter characterized by reduced salivary flow (70,71).…”
Section: Role Of Saliva In Covid-19 Pathogenicity and Disease Diagnosismentioning
confidence: 99%
“…In COVID-19, the impaired salivary gland secretions are often associated with xerostomia and taste loss (69). Xerostomia is the subjective complaint of oral dryness, while salivary gland hypofunction is an objective matter characterized by reduced salivary flow (70,71).…”
Section: Role Of Saliva In Covid-19 Pathogenicity and Disease Diagnosismentioning
confidence: 99%
“…The current evidence indicates that a substantial portion of patients with COVID-19 develop dysphagia during the course of the disease [ 3 5 ]. In particular, dysphagia appears frequent among patients admitted to intensive care due to COVID-19 infection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral health may adversely influence other parts of the body. Recent studies showed that oral manifestations are commonly noticed in about 45% of COVID-19 patients [ 24 , 25 , 26 ]. Salivary glands, tonsils, and tongue are highly sensitive for SARS-CoV-2 infection [ 27 , 28 , 29 ].…”
Section: Mechanism Of Infection In Oral and Overall Body Healthmentioning
confidence: 99%